Progranulin as a therapeutic target in neurodegenerative diseases. (August 2022) - Rhinn, Herve; Tatton, Nadine; McCaughey, Stella; Kurnellas, Michael; Rosenthal, Arnon
Abstract : Progranulin (PGRN, encoded by the GRN gene) plays a key role in the development, survival, function, and maintenance of neurons and microglia in the mammalian brain. It regulates lysosomal biogenesis, inflammation, repair, stress response, and aging. GRN loss-of-function mutations cause neuronal ceroid lipofuscinosis or frontotemporal dementia- GRN (FTD- GRN ) in a gene dosage-dependent manner. Mutations that reduce PGRN levels increase the risk for developing Alzheimer's disease, Parkinson's disease, and limbic-predominant age-related transactivation response DNA-binding protein 43 encephalopathy, as well as exacerbate the progression of amyotrophic lateral sclerosis (ALS) and FTD caused by the hexanucleotide repeat expansion in the C9orf72 gene. Elevating and/or restoring PGRN levels is an attractive therapeutic strategy and is being investigated for neurodegenerative diseases through multiple mechanisms of action. Highlights: Progranulin (PGRN) is a secreted, immune regulatory protein produced by myeloid cells and some neurons that regulates lysosomal function, neuronal survival, and inflammation. GRN loss-of-function mutations cause neuronal ceroid lipofuscinosis and frontotemporal dementia- GRN (FTD- GRN ) in a dosage-dependent manner. Mutations that reduce PGRN levels are also associated with higher risk for amyotrophic lateral sclerosis (ALS) and FTD caused by the hexanucleotide repeat expansion in the C9orf72 gene, Parkinson's disease (PD), Alzheimer's disease (AD), limbic-predominant age-related transactivation response DNA-binding protein 43 (TDP-43) encephalopathy, Gaucher disease, and autism. PGRN overexpression is protective in animal models for AD, PD, FTD, ALS, stroke, Gaucher disease, and arthritis. PGRN is being investigated as a therapeutic target for neurodegenerative diseases through multiple mechanisms of action.